2013
DOI: 10.1515/jpem-2012-0303
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor as an indicator of neonatal maturity

Abstract: Hepatocyte growth factor (HGF) is a potent mitogen and morphogen expressed in fetal organs. It requires activation by specific serine proteases. The role of activated HGF during fetal development has not been evaluated. We hypothesized that the serum levels of activated HGF would be increased in preterm neonates. Cord blood total HGF and activated HGF levels were measured in 19 preterm (gestational age, 28.04±2.39 weeks) and 24 term (gestational age, 39.37±0.95 weeks) newborns. Anthropometric parameters and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…HGF regulates cell proliferation, cell survival, and angiogenesis (47), which are especially important in enterocytes (48). In our study, we found that HGF expression was inversely correlated to BW and a tendency toward it being inversely correlated to GA. Inverse correlation of GA and HGF expression has been found previously (49) and would be in line with the fact that increased prematurity increases risk for NEC (15). Protein levels are higher in the second trimester as compared with levels found in urine from newborns (50).…”
Section: Discussionsupporting
confidence: 82%
“…HGF regulates cell proliferation, cell survival, and angiogenesis (47), which are especially important in enterocytes (48). In our study, we found that HGF expression was inversely correlated to BW and a tendency toward it being inversely correlated to GA. Inverse correlation of GA and HGF expression has been found previously (49) and would be in line with the fact that increased prematurity increases risk for NEC (15). Protein levels are higher in the second trimester as compared with levels found in urine from newborns (50).…”
Section: Discussionsupporting
confidence: 82%
“…These results are in disagreement with the notion that in obese patients serum HGF associated with obesity [9,11] and had a linear relationship with BMI [9]. Finally, total-HGF and activated-HGF blood levels in neonates are regulated in a time-dependent manner along fetal development [22].…”
mentioning
confidence: 56%
“…Placental HGF has been reported to be strongly expressed in the villous syncytium, extravillous trophoblast, and amnionic epithelium ( 32 ). In umbilical vein blood, an increase of HGF levels throughout normal pregnancies has been found ( 33 ), although there might instead be an inverse correlation between activated HGF and gestational age ( 34 ). Furthermore, in healthy women with normal pregnancies HGF in maternal plasma has been shown to be upregulated in the third trimester and then downregulated postpartum ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no associations have previously been found regarding maternal plasma levels of HGF and PTB. However, higher levels of activated HGF have been found in the cord blood of preterm infants compared to term neonates, although total HGF levels did not differ ( 34 ).…”
Section: Discussionmentioning
confidence: 99%